Detection of chromosomal translocation [T(12;21)] and regulatory T cells in acute leukaemias using flow cytometry - Idris, Siti Zuleha (2013)
Leukaemia is a haematological malignancy detected in blood and bone marrow. Children achieve a 10-year survival rate of more than 85% but the prognosis for adult leukemia remains poor. Due to the heterogeneity of this disease a combination of laboratory techniques is needed for the classification and diagnosis of leukemias including cell morphology, cytochemistry, immunophenotype and cytogenetics. Cytogenetics provide information on treatment outcome. It is also a specific and personalized method for monitoring of minimal residual disease. The first chromosomal abnormality recognized was t(9;22) or BCR/ABL in chronic myeloid leukaemia (CML) by Nowell and Hungerford in 1959. Today more than 50 translocations have been reported and are essential in diagnosing and monitoring treatment outcome in leukaemia. Current methods used to detect and identify chromosomal translocations have some disadvantages. Conventional karyotyping method is a laborious procedure, insensitive (inadequate metaphase spreads, poor chromosome morphology) and need skilled technical staff whereas fluorescent in situ hybridization (FISH) and array comparative genomic hybridization (aCGH) are expensive tests. Polymerase chain reaction (PCR)-based kits are available however do not provide information on individuals cells of a mixed population, typical of clinical samples. Flow cytometry is a powerful equipment for rapid and multiparametric analysis of single cells providing both quantitative and qualitative information on size, internal complexity of cells and expression of markers by fluorescence labeled specific antibodies. Currently its usage is limited to determining lineage specificity of leukaemias (i.e. antigen expressions) while treatment monitoring (minimal residual disease) involves a panel of markers which overlap with normal blasts. The principle purpose of minimal residual disease is the detection of a rare population of leukemia blast whether immediately after treatment (for possible drug resistance) or after remission (for impending relapse). This will provide guidance on treatment. In-situ reverse transcriptase-polymerase chain reaction (RT-PCR) is a technique where cDNA is amplified within the cell. By combining these two methods and use of fluorescent primers, it is possible to detect chromosomal translocations within single cells using flow cytometry. The multiparametric potential of flow cytometry also allows the detection of rare cell populations with complex phenotypes such as regulatory T cells (Tregs). Tregs function by downregulating immune activation. However, this may also suppress the cancer immunosurveillance processes. Significantly increased numbers of Tregs has been reported in various cancers and has been suggested as a possible aetiology of acute leukaemias. Objectives of this study were to establish a method for in situ RT-PCR to detect chromosomal translocations in leukaemia and determine Tregs percentages using flow cytometry. Eighty acute leukaemia samples (44 acute myeloid leukaemia, 34 acute lymphocytic leukaemia, two mixed acute leukaemia) were screened for t(12;21) and t(8;21) using reverse transcriptase polymerase chain reaction (RT-PCR) method. Fifteen or 18% acute leukaemia samples were positive for t(12:21) and eight were positive in ALL cases. The t(8;21) translocation was detected in only two (2.5%) AML samples but in none of the ALL or mixed leukaemias. Twelve (80%) of the positive t(12;21) samples were analyzed using in situ RT-PCR and showed 80-97% positive cells with fluorescence phosphorammidite (FAM) labeled primers and detected by flow cytometry. Three colour staining was then performed by adding leukaemia markers (CD45PerCP and CD19PE or CD13PE) after in situ RT-PCR method which identified 50-90% positive cells. Tregs identified by the CD3+CD4+CD25+CD127- phenotype was found to be significantly higher in ALL samples (17 ALL samples) when compared to normal (30 normal healthy samples). In situ RT-PCR method may help in the investigation, diagnosis and monitoring of leukaemia by detecting chromosomal translocations specific to the patient. Multiparametric staining with markers of interest will further identify specific leukaemia populations and provide additional information that may help in disease management. In situ RT-PCR flow cytometry techniques have potential to be further developed and implemented in pathology services. Tregs may be important in immunosurvellance and cancer escape mechanism (pathogenesis of acute leukaemias) and could be used as targets for alternative therapy.